(untitled) (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: This cross-sectional study was conducted from April to July 2012 to estimate the prevalence of brucellosis and investigate the risk factors that enhance its occurrence in cattle in Khartoum state, the Sudan. Material and methods: A total of 300 serum samples were taken from jugular veins of cattle and screened by Rose Bengal Plate Test (RBPT) and Serum Agglutination Test (SAT). The RBPT-positive samples were all tested using c-ELISA. Results: Antibodies were detected with an overall seroprevalence of 25.7% using RBPT and 22.7% using SAT while slightly less than two thirds of the RBPT-positive samples were cELISA-positive. The herd and within-herd seroprevalences were 76.7% (n=23) and from 10.0-80.0%. Moreover, significant statistical dissimilarities were not observed between the seroprevalence of the different categories of the investigated risk factors by RBPT. Only milking method (?2=3.976; P=0.046) was found to have an influence on the RBPT-positive status for brucella infection in the univariate analysis. Additionally, natural breeding (OR=3.61; 95% CI 1.19210.96; P=0.023) was the only observed risk factor with an increased odd of being RBPT positive. The Kappa analysis showed an almost perfect agreement between the results of the RBPT and the SAT tests. Conclusion: The prevalence of anti-brucella antibodies in Khartoum state was relatively higher; therefore, brucellosis in cattle is, perhaps, a significant public health problem. It is recommended to raise awareness of cattle owners and/or herders on the routes of transmission of brucellosis. http://doi.org/10.5455/javar.2016.c141